Additional prognostic value of electrocardiographic left ventricular hypertrophy in traditional cardiovascular risk assessments in chronic kidney disease. Issue 6 (June 2020) - Tanaka, Fumitaka; Komi, Ryosuke; Nakamura, Motoyuki; Tanno, Kozo; Onoda, Toshiyuki; Ohsawa, Masaki; Sakata, Kiyomi; Omama, Shinichi; Ogasawara, Kuniaki; Ishibashi, Yasuhiro; Yonekura, Yuki; Itai, Kazuyoshi; et al.
Abstract : Background: Left ventricular hypertrophy (LVH) is a common predictor of the cardiovascular prognosis in chronic kidney disease (CKD). However, whether or not electrocardiography-derived LVH (ECG-LVH) has prognostic value in patients with various degrees of CKD and improves the cardiovascular risk stratification based on traditional risk factors remains unclear. Methods: A total of 7206 participants at least 40 years of age who were free from cardiovascular events in a general population were followed for the incidence of cardiovascular events. CKD was confirmed by either the presence of a reduced estimated glomerular filtration rate (eGFR) (<60 ml/min per 1.73 m 2 ) or albuminuria, defined as a urinary albumin-to-creatinine ratio (UACR) of at least 30 mg/g Cr. Results: A total of 1886 (26.2%) had CKD, of which 1471 (78.0%) had a preserved eGFR (CKD stage 1–2). After an average 11.3 years of follow-up, the adjusted hazard ratio for the incidence of cardiovascular events significantly increased for ECG-LVH according to the Sokolow–Lyon voltage, Cornell voltage, or Cornell voltage product among participants with CKD (hazard ratio 1.47, P = 0.002), in contrast to those without CKD (hazard ratio 1.15, P = 0.210). The inclusion of any ECG-LVH parameters improved the accuracy of reclassification in any risk prediction model based on the eGFR, UACR, or Framingham 10-year risk score in the CKD participants (net reclassification improvement = 0.13–0.32, all P values <0.040). Conclusion: In patients with CKD stage 1–5, ECG-LVH is useful for predicting the risk of future cardiovascular events and adds prognostic information to traditional cardiovascular risk assessments.